2021
DOI: 10.1111/vde.12995
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia otitis unresponsive to primary care: outcome in 59 dogs

Abstract: Background Otitis externa (OE) is a common disorder in dogs. Infection by the commensal yeast, Malassezia pachydermatis, may result in chronic disease that does not respond to standard primary care. Chronic infectious OE may be associated with otitis media (OM). Hypothesis/Objective To report medical management, clinical outcomes and frequency of middle ear involvement, in dogs with Malassezia otitis unresponsive to primary care. Animals Fifty‐nine dogs from one referral veterinary hospital from January 2007 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…A mixed infection also was seen frequently, as reported in other studies 32,35,36 . Labrador and Golden retrievers were the most common breeds in this study, as seen in other studies 24,30,35,36 This is not surprising because OE is a frequent clinical sign of atopic dermatitis and both breeds are predisposed to this disease 37,38 . It has been shown that allergies are one of the most common skin complaints in small animal practice in Germany and our findings correspond to this 39…”
Section: Discussionsupporting
confidence: 91%
“…A mixed infection also was seen frequently, as reported in other studies 32,35,36 . Labrador and Golden retrievers were the most common breeds in this study, as seen in other studies 24,30,35,36 This is not surprising because OE is a frequent clinical sign of atopic dermatitis and both breeds are predisposed to this disease 37,38 . It has been shown that allergies are one of the most common skin complaints in small animal practice in Germany and our findings correspond to this 39…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of infection as sole causative agent is reported between 8% and 26% [ 4 , 5 ]. Some dogs appear to develop an allergic response to Malassezia spp., leading to significant discomfort and pruritus [ 1 ] and, when not properly treated the affection can evolve in otitis media, as well [ 6 ]. Therefore, an effective therapy, together with the correction of predisposing factors and concurrent diseases, is mandatory to prevent relapses [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, yeast has also been associated with middle ear disease and identified in 23.7% of cases with otitis media [14]. More recently, Malassezia otitis media was diagnosed in 17% of cases of chronic Malassezia otitis by otoscopy and sampling of middle ear content in 14 cases [15]. There was evidence of soft tissue attenuation material in the tympanic bulla on CT imaging in 4 of those cases [15].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Malassezia otitis media was diagnosed in 17% of cases of chronic Malassezia otitis by otoscopy and sampling of middle ear content in 14 cases [15]. There was evidence of soft tissue attenuation material in the tympanic bulla on CT imaging in 4 of those cases [15]. In reflection, myringotomy, imaging, fungal culture and microbiome studies could have brought more information about lesion extension and the mycobiota of the SMO.…”
Section: Discussionmentioning
confidence: 99%